Biomonitoring of metal(oid)s in mining-affected Borcka Dam Lake coupled with public health outcomes - Gedik, Kenan; Terzi, Ertugrul; Yesilcicek, Tuncay (Informa UK Limited, 2018)
Due to increased anthropogenic activities, the aquatic environment is exposed to pollutants much more than ever. These pollutants go into the food chain and can pose a health risk to human. Correla...
Keywords: 13. Climate action; 6. Clean water; 3. Good health